Relações intergovernamentais, federalismo e políticas públicas: decisões intergovernamentais verticais no âmbito das políticas de saúde e assistência social no Brasil - José Geraldo Leandro Gontijo (2015)
The thesis analyzes in comparative form vertical intergovernmental relations (between the three levels of government) in national health and social assistance policies after 1988 in Brazil, focused: on (i) structures and rules established for the production of joint decisions between the federal entities; (ii) the dynamic of relations between actors, forged from the trajectory of the subsystems of each policy sector; and (iii) the dynamics of the relationship between the three levels of government, which developed from the structures and rules. We work with the hypotheses that: (1) national health and social assistance policies have similar structures and formal decision-making rules for the production of joint decisions between levels of government. But that (2) because of the political nature and the particularities of their respective subsystems, in the case of the Unified Health System, such rules are observed in the production of decisions related to all its internal faces while under the Unified Social Assistance, decisions about some kind of interventions pass the shores of the decision-making areas established for deliberation and agreement between levels of government. Additionally, we operationalized also (3) the thesis that in Brazil after 1988, the decision-making power over public policy remained concentrated at the federal level of government, leaving the governmental subunits, in most cases, the role of implementing policies (policy-making) with limited possibilities to influence decisions. We adopted as methodological strategies: the documental analysis and semi structured interviews. The findings indicate the confirmation of the hypotheses that guided the study.